Pemeriksaan Kadar Glukosa, Asam Urat dan Kolesterol Universitas Pertahanan RI Di Muara Angke - Ibrizatun, Amin; Pujowaskito, Prihati; Wibowo, Markus; Yochannan, Elisa; Pannyiwi, Rahmat; Sipahutar, Pongki; Wijayanti, Azmi; Wahyudin, Ferdic Sukma; Sofiana, Sofiana (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
The Ministry of Health stated that non-communicable diseases cause high mortality rates each year and can infect individuals of all ages and countries around the world. Non-communicable diseases include heart disease, diabetes mellitus and kidney disease. To overcome these health problems, preventive measures are needed that aim to improve the quality of life of the nation. This is stated in the Presidential Instruction which is one part of the meaning of Germas, namely routine health checks that are useful for facilitating early detection of diseases or health problems. The examinations carried out are divided into 2, namely examination of random blood sugar levels, uric acid, and cholesterol levels and EKG (Electrocardiography) examinations. The purpose of community service is to provide information on the results of examinations of random blood sugar levels, uric acid, and cholesterol levels by the PkM TEAM from Lecturers together with Cadets of the Indonesian Defense University for the people of Muare Angke in improving health. The method is by examining random blood sugar levels, uric acid and cholesterol. The results concluded that most respondents had normal blood sugar levels, uric acid levels, and cholesterol levels.